A neonicotinoid insecticide reduces fueling and delays migration in songbirds - Eng, Margaret L; Stutchbury, Bridget J M; Morrissey, Christy A (Science (American Association for the Advancement of Science), 2019)
Neonicotinoids are neurotoxic insecticides widely used as seed treatments, but little is known of their effects on migrating birds that forage in agricultural areas. We tracked the migratory movements of imidacloprid-exposed songbirds at a landscape scale using a combination of experimental dosing and automated radio telemetry. Ingestion of field-realistic quantities of imidacloprid (1.2 or 3.9 milligrams per kilogram body mass) by white-crowned sparrows ( ) during migratory stopover caused a rapid reduction in food consumption, mass, and fat and significantly affected their probability of departure. Birds in the high-dose treatment stayed a median of 3.5 days longer at the site of capture after exposure as compared with controls, likely to regain fuel stores or recover from intoxication. Migration delays can carry over to affect survival and reproduction; thus, these results confirm a link between sublethal pesticide exposure and adverse outcomes for migratory bird populations.